Pengaruh Pelatihan Dan Pengembangan SDM Terhadap Kinerja Pegawai Dinas Pemadam Kebakaran Dan Penyelamatan Kota Cilegon: The Effect of HR Training and Development on Employee Performance Cilegon City Fire and Rescue Service - Popon Fauziah; Ratih Hastasari; Wawan Saputra (CV Warnak Johanna Nusantara, 2026)
The purpose of this study is to determine the influence of training and human resource development on the performance of employees at the Cilegon City Fire and Rescue Service The sample in this study uses taking objects from samples called sampling. So for sampling, the formula used is the slovin formula. distributed questionnaires to employees as many as 92 respondents. The researcher uses statistical quantitative research methods and applications that will be used to process data in this study using the IBM SPSS statistical application version 21. The results of this study show that training has a positive and significant effect on employee performance by 0.16 and human resource development has a positive and significant effect on employee performance by 0.000. Therefore, training and human resource development together affect employee performance with a value of 0.000 and the value of the simultaneous determination coefficient in this study, which is R square of 0.463 or 46.3%. This means that employee performance is influenced by 46.3% by HR training and development while the rest is influenced by other variables that are not studied in this study. It is recommended for subsequent researchers to expand the scope of variables and samples so that the results can be more general and can be applied widely in other organizational contexts